PENINGKATAN KOMPETENSI KARYAWAN PERUSAHAAN FARMASI MELALUI PELATIHAN PERENCANAAN MANAJEMEN BISNIS - Ana Kadarningsih; Dian Prawitasari; Endang Setyowati (Jurnal Padamu Negeri, 2026)
The pharmaceutical industry is a critical sector in every developed and developing country. The pharmaceutical industry is a key asset for the global economy, so pharmaceutical companies need business management planning for company survival. This business management planning includes marketing management planning, financial management, human resource management and operational management. Business management planning requires the ability and competence of human resources or pharmaceutical company employees, so training is needed to improve the ability of pharmaceutical company employees to prepare business management plans so that they are effective and efficient based on a success metric system. This business management planning training was given to managers and supervisors of pharmaceutical companies in the city of Semarang and Semarang Regency, a total of 45 participants from 22 pharmaceutical companies. The training activity stage consists of three activities, including presentation of business management material, practical business management planning exercises and training evaluation. Apart from that, before the training, a pretest and posttest were carried out after the training. The results of the business management planning training activities showed that participants' understanding of business management increased by 40% after the training was implemented.  Apart from that, training participants are able to prepare marketing management plans, financial management, human resource management and operational management that are more effective and efficient.